Recommendations Improving the Linkage between Lac Hong University and Enterprises in Dong Nai Province - Dung, Tran (Social Science Learning Education Journal, 2017)
The linking between Universities and enterprises is an objective requirement based on the principles of education: Learning with practice, education combined with productive labor, education of University attached